Bank relationships and small firms' financial performance - Annalisa Castelli; Jr. Gerald P. Dwyer; Iftekhar Hasan (Federal Reserve Bank of Atlanta, 2006)
We examine the relationship between the number of bank relationships and firms' performance, evaluating possible differential effects related to firms' size. Our sample of firms from Italy includes many small firms, 99 percent of which are not listed and for which bank debt is a major source of financing. In the sample, 4 percent of the firms have a single bank relationship, and 66 percent of them have five or fewer relationships. We find that return on equity and return on assets decrease as the number of bank relationships increases, with a stronger relationship for small firms than for large firms. We also find that interest expense over assets increases as the number of relationships increases. Particularly for small firms, our results are consistent with analyses indicating that fewer bank relationships reduce information asymmetries and agency problems, which outweigh negative effects connected to holdup problems.
Keywords: 330; Bank; Kreditgeschäft; KMU; Unternehmenserfolg; Italien